FOOD CONSUMPTION AND HEALTH IN ITALY: THE ROLE OF INNOVATION - Cesaretti Gian, Paolo; Annunziata, Azzurra; Ardeleanu Monica, Patricia; Carbone, Graziella; Scarpato, Debora; Vecchio, Riccardo (Economics of Agriculture, 2011)
During the last years, the increasingly close link between health and nutrition and the spread of chronic diseases, are emerging the need to develop innovative practices, due to ensure health and wellness to the community and also to guarantee more competitiveness to the agri-food sector. This paper aims to underline the central role of the innovation as an essential tool to meet the new needs expressed by consumers and to answer at the health problems related to nutrition. The work is part of the research project "In.be.sa" conducted by the University of Naples "Parthenope".